KELAYAKAN USAHA BUDIDAYA UDANG VANAME (Litopenaeus vannamei) DI DESA PURWOREJO, KECAMATAN PASIR SAKTI KABUPATEN LAMPUNG TIMUR - Muhammad Mutakin; Supono Supono; Yudha Trinoegraha Adiputra (University of Lampung, 2019)
Shrimp cultured in Purworejo Village begun in the 1980s. Productivity of shrimp farming in this region, had experienced a peak of success in 1998 with an average production of 200 kg / ha with black tiger shrimp (Penaeus monodon) as the main commodity. Productivity decreases to 120kg / ha then occur due to decreasing environmental quality and susceptible post larvae to disease infections. One effort to increase the productivity of ponds can be done by switching the cultivation of black tiger shrimp to Pacific white leg (Litopenaeus vannamei) shrimp. The purpose of this study was to study the feasibility of semiintensive Pacific whiteleg shrimp cultured. This research was carried out in two shrimp farmer groups namely Sido Makmur and Lestari Gemilang located in Purworejo Village, Pasir Sakti District, East Lampung Regency. The type of research used is a case study and uses descriptive tests. The results showed that Pacific white leg shrimp cultured can produce 10,804,45 kg/3 ha and achieve a profit of Rp. 407.025.500 with a net B/C of 1,7. Moreover, black tiger shrimp culturehas reached 725 kg/5 ha with a profit of Rp. 13.660.000 with net B/C of 1,2. This study concluded semiintensive Pacific whiteleg shrimp is profitable compared toblack tiger shrimp cultured. It is also feasible to be developed by the village community.